BIO-RESIDUAL STUDIES AND TREATING GUNNY SACKS WITH COUMARINS EXTRACT ON SEED PROTECTION AGAINST COWPEA BEETLE, CALLOSOBRUCHUS MACULATUS (FAB.) - I. A., Ismail; Abdel-Rahman, R.S. (European Scientific Journal, ESJ, 2015)
Cowpea beetle, Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), is the most important storage pest of cowpea. The quantification of cowpea losses through C. maculatus is very desirable. Coumarins possess controlling cowpea beetle. Both Ethanol and Chloroform extracts of Murraya, Kumquat and Celery plants were studied. Murraya ethanol extracts was more efficient than chloroform, as it induces higher percentage of reduction in the progeny, also protects cowpea seeds till 6 months when using the higher concentration (4%). Gunny sacks were treated with different extracts of the three of plants as an application method for protecting stored grain from infestation and ethanol extracts was a more effective than chloroform. The effect of the extracts on the weight loss of cowpea seeds was studied. The reduction percentage in weight increased from zero to 13% and 17.10% after nine months for both chloroform and ethanol kumquat extracts, respectively at the higher concentration used.